Proposta e validação de solução de computação em nuvem para redes com dispositivos nacionais - Zugliani, Ettore (Universidade Federal de São Carlos, 2016)
Cloud and virtualization are both recurring subjects, today they are used in a variety of systems in oder to provide solutions that are effective, scalable, with easier maintenance and les costly. Among the main names of the area we have the OpenStack software which provides various levels of virtualization from virtual machines to virtual networks, OpeStack code is open source and it‘s network module, Neutron, has the support of several manufactors like Cisco, Brocade and Arista but untill now there is no support for a national manufactor. This work proposes the construction of a national solution for network virtualization, proposing the construction of a driver for the OpenStack network module that supports the equipments of the brazilian manufactor Datacom. This text features first a overview of the actual environment of cloud computing, a study about OpenStack and it‘s network module Neutron, and them taking this study as starting point a set of diagrams are presented in order to propose a solution. This solution is them built using the programing language Python and good practices of programing and them at the end of te implementation presents a solid and highly modular solution. Therefore this proposal is validated through a series of unity tests which are necessary for the approval of the code by the comunity. This work results in a working OpenStack environment using the UFSCar servers, which comunicates in a satisfactory manner with national network equipments, besides the contribution with OpenStack development.
Keywords: Redes; Computação em nuvem; Virtualização; OpenStack; Neutron; Networks; Cloud computing; Virtualization; Python; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO